THEME ANALYSIS AS A TOOL TO TEACH COHESIVE ENGLISH TEXTS - Budi Rahayu (FKIP Universitas Cenderawasih, 2022)
The fact shows that teaching writing English as a foreign language in Indoneia is not easy. The studentsâ€™ problems seem to be related to grammar, vocabulary, genre and mostly cohesion. Â We should always find appropriate better ways to solve this problem. One of the ways to solve this problem may be the application of Â Systemic Fumctional Linguistics, especially the use of Theme in shaping a cohesive text. It is shaped by making the Theme of the clause be related with the Theme or the Rheme of the previous clauses.Keywords: Theme, Rheme, Clause, Cohesion